Circulating extracellular vesicles in healthy and pathological pregnancies: A scoping review of methodology, rigour and results - Megan V. C. Barnes; Paschalia Pantazi; Beth Holder (Journal of Extracellular Vesicles, 2023)
Abstract Extracellular vesicles (EVs) play a crucial role in pregnancy, revealed by the presence of placental‐derived EVs in maternal blood, their in vitro functionality, and their altered cargo in pregnancy pathologies. These EVs are thought to be involved in the development of pregnancy pathologies, such as pre‐eclampsia, pre‐term birth, and fetal growth restriction, and have been suggested as a source of biomarkers for gestational diseases. However, to accurately interpret their function and biomarker potential, it is necessary to critically evaluate the EV isolation and characterization methodologies used in pregnant cohorts. In this systematic scoping review, we collated the results from 152 studies that have investigated EVs in the blood of pregnant women, and provide a detailed analysis of the EV isolation and characterization methodologies used. Our findings indicate an overall increase in EV concentrations in pregnant compared to non‐pregnant individuals, an increased EV count as gestation progresses, and an increased EV count in some pregnancy pathologies. We highlight the need for improved standardization of methodology, greater focus on gestational changes in EV concentrations, and further investigations into the functionality of EVs. Our review suggests that EVs hold great promise as diagnostic and translational tools for gestational diseases. However, to fully realize their potential, it is crucial to improve the standardization and reliability of EV isolation and characterization methodologies, and to gain a better understanding of their functional roles in pregnancy pathologies.